TREATMENT OUTCOMES FOR NEWBORNS WITH CONGENITAL DIAPHRAGMATIC HERNIA - Huseynov, F.R.; Gasimov, A.Sh. (World of Medicine and Biology, 2025)
The purpose of the study was to assess the results of surgical treatment of newborns with congenital diaphragmatic hernia based on a set of clinical, cardiological and quality of life indicators. The study included 70 newborns diagnosed with congenital diaphragmatic hernia. Depending on the method of surgical intervention, the children were divided into 2 groups. The comparison group consisted of 44 newborns operated on using the traditional open method, and the main group consisted of 26 newborns operated on using a new minimally invasive surgical technique – endosurgery. The study showed that the method of surgical intervention proposed by us allows to reduce the length of stay in the clinic, quickly improve the condition of children, and return quality of life indicators to normal.
Keywords: congenital diaphragmatic hernia; newborns; surgery; quality of life; clinic